2006
DOI: 10.1007/s00436-005-0111-x
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-conjugating enzyme genes in Oesophagostomum dentatum

Abstract: Full-length genes representing different isoforms of the ubiquitin-conjugating enzyme UBC-2 were isolated from Oesophagostomum dentatum, cloned and sequenced. The alignment of their sequences (designated Od-ubc-2.1 to Od-ubc-2.3) revealed nucleotide variation at three positions within the predicted open reading frame of 444 bp. Substitutions were at positions 141 (A<-->G), 142 (A<-->G) and 296 (T<-->C). Both former substitutions resulted in amino acid changes from a glycine residue to an arginine residue, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…7) between Tv-ant-1 and tag-61, we were not able to specifically silence tag-61 in C. elegans by feeding. This outcome is consistent with some previous findings for other genes from strongylid nematodes (Cottee et al, 2006;Hu et al, unpublished data) and indicates that the criteria (cf. Gao et al, 2006) or experimental conditions used herein may be inadequate to achieve effective gene silencing in C. elegans using the parasite homologue/orthologue Tv-ant-1.…”
Section: Discussionsupporting
confidence: 94%
“…7) between Tv-ant-1 and tag-61, we were not able to specifically silence tag-61 in C. elegans by feeding. This outcome is consistent with some previous findings for other genes from strongylid nematodes (Cottee et al, 2006;Hu et al, unpublished data) and indicates that the criteria (cf. Gao et al, 2006) or experimental conditions used herein may be inadequate to achieve effective gene silencing in C. elegans using the parasite homologue/orthologue Tv-ant-1.…”
Section: Discussionsupporting
confidence: 94%
“…We confirmed that Peo lacks the catalytic cysteine of E2 enzymes. In addition, 8 residues before the catalytic cysteine site, Peo exhibits an HPH tripeptide ( S2 Fig ) instead of HPN, which is a canonical signature of the E2 superfamily [ 41 ]. Peo contains a UEV domain of ~150 amino acids resembling the canonical E2 fold in its hydrophobic core and active site region.…”
Section: Resultsmentioning
confidence: 99%
“…The primers amplified a product of 399 bp in the variable region in exons 3 to 7 (see Results section) for both isotypes. As Normalizer the housekeeping gene ubiquitin-conjugating enzyme 2 (OD-ubc-2 ; product size : 444 bp) was amplified as described (Cottee et al 2006) in 20 ml of pre-manufactured master mixes (Power SYBR 1 Green PCR Master Mix ; Applied Biosystems, Brunamgebirge, Austria) using the same cycling conditions as above. For all stages 2 cDNA preparations were tested except L3c (1 preparation) ; each sample was tested in 2 independent PCR runs, each in duplicate (i.e.…”
Section: Expression Analysis Of Gst Isotypesmentioning
confidence: 99%